Dynamics of Tryptophan Metabolic Pathways in Human Placenta and Placental-Derived Cells: Effect of Gestation Age and Trophoblast Differentiation - Karahoda, Rona (Front Cell Dev Biol, 2020)
L-Tryptophan is an essential amino acid and a precursor of several physiologically active metabolites. In the placenta, the serotonin and kynurenine metabolic pathways of tryptophan metabolism have been identified, giving rise to various molecules of neuroactive or immunoprotective properties, such as serotonin, melatonin, kynurenine, kynurenic acid, or quinolinic acid. Current literature suggests that optimal levels of these molecules in the fetoplacental unit are crucial for proper placenta functions, fetal development and programming. Placenta is a unique endocrine organ that, being equipped with a battery of biotransformation enzymes and transporters, precisely orchestrates homeostasis of tryptophan metabolic pathways. However, because pregnancy is a dynamic process and placental/fetal needs are continuously changing throughout gestation, placenta must adapt to these changes and ensure proper communication in the feto-placental unit. Therefore, in this study we investigated alterations of placental tryptophan metabolic pathways throughout gestation. Quantitative polymerase chain reaction (PCR) analysis of 21 selected genes was carried out in first trimester (n = 13) and term (n = 32) placentas. Heatmap analysis with hierarchical clustering revealed differential gene expression of serotonin and kynurenine pathways across gestation. Subsequently, digital droplet PCR, Western blot, and functional analyses of the rate-limiting enzymes suggest preferential serotonin synthesis early in pregnancy with a switch to kynurenine production toward term. Correspondingly, increased function and/or protein expression of serotonin degrading enzyme and transporters at term indicates efficient placental uptake and metabolic degradation of serotonin. Lastly, gene expression analysis in choriocarcinoma-derived cell lines (BeWo, BeWo b30, JEG-3) revealed dissimilar expression patterns and divergent effect of syncytialization compared to primary trophoblast cells isolated from human term placentas; these findings show that the commonly used in vitro placental models are not suitable to study placental handling of tryptophan. Altogether, our data provide the first comprehensive evidence of changes in placental homeostasis of tryptophan and its metabolites as a function of gestational age, which is critical for proper placental function and fetal development.